The wealth decumulation behavior of the retired elderly in Japan: The relative importance of precautionary saving and bequest motives - Yoko Niimi; Charles Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This paper analyzes the determinants of the wealth decumulation behavior of the retired elderly in Japan using unique information from two household surveys, and by so doing, attempts to assess the relative importance of precautionary saving and bequest motives in explaining the lower than expected rates of wealth decumulation of the retired elderly. Taken together, our analyses of these two datasets show that precautionary saving plays a relatively important role in explaining the lower than expected wealth decumulation rate of the retired elderly, at least in the case of Japan, even though both precautionary saving and bequest motives are important drivers behind this puzzle. Our results also suggest the possibility that financial burden of parental care may also affect the wealth decumulation behavior of the retired elderly in Japan. Given that parental care responsibilities tend to arise relatively late in life, often after retirement, in the case of Japan, our results suggest that the financial burden of parental care may be a relevant issue when analyzing the wealth decumulation behavior of the elderly.
Keywords: D14; D15; D64; E21; J14; 330; Aged; bequests; dissaving; Japan; life-cycle model; precautionary saving; retired elderly; saving; wealth decumulation